2023
DOI: 10.1039/d3ra00399j
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the effect of crystallinity and particle size of biogenic Ag/ZnO nanocomposites on the electrochemical sensing performance of carbaryl detection in agricultural products

Abstract: We have investigated the green synthesis of Ag/ZnO nanocomposites via a microwave-assisted/biogenic electrochemical method with mangosteen peel extract. Ag/ZnO-based sensing platform has been proposed for carbaryl detection in agriculture products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…The absorption capacity of each modified electrode can be calculated from the values of the observed slope of I pa versus v for SPCE-A400, SPCE-A600, and SPCE-A800 being 3.18 × 10 –5 , 2.2 × 10 –5 , and 1.22 × 10 –5 mol cm –2 , respectively. In comparison, previous works have determined the value of adsorption capacity of electrochemical sensors based on modified electrodes for carbaryl detection and obtained comparable results with our work. , Based on these results, it can be concluded that the modified electrodes based on SPCE-modified AuNR400 displayed the largest capacity for carbaryl adsorption on the electrode surface among other developed electrodes.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The absorption capacity of each modified electrode can be calculated from the values of the observed slope of I pa versus v for SPCE-A400, SPCE-A600, and SPCE-A800 being 3.18 × 10 –5 , 2.2 × 10 –5 , and 1.22 × 10 –5 mol cm –2 , respectively. In comparison, previous works have determined the value of adsorption capacity of electrochemical sensors based on modified electrodes for carbaryl detection and obtained comparable results with our work. , Based on these results, it can be concluded that the modified electrodes based on SPCE-modified AuNR400 displayed the largest capacity for carbaryl adsorption on the electrode surface among other developed electrodes.…”
Section: Resultssupporting
confidence: 86%
“…The mechanism of carbaryl oxidation on the surface of SPCE-modified AuNRs can be deduced following the two processes: (1) the hydrolysis of carbaryl molecules into 1-naphthol in an alkaline condition and (2) the oxidation of hydroxyl (OH – ) functional groups within the 1-naphthol chemical structure by removing 1 electron and 1 proton (H + ) with the corresponding anodic oxidation peak at 0.2 V. The mechanism of carbaryl oxidation at the surface of SPCE-modified AuNR is illustrated in Figure d. Furthermore, recent studies demonstrated the oxidation of 1-naphthol using SPCE-modified metal nanoparticles, and the metal oxide composite occurs at 0.4 V as reported in ref and at 0.5 V as reported in ref . Based on this result, it can be inferred that the SPCE-modified facet-controlled anisotropic gold nanoparticles provide faster electron transfer kinetics to oxidize carbaryl molecules than bare SPCE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation